Colombia and Venezuela: two countries, one people A comparative analysis of the evolution of the Human Development Index - Muñoz Téllez , John Maximino; Bernal Gómez, Daniel Rigoberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper is a review and comparative analysis of the human development index between the States of Colombia and Venezuela, which invites us to make a quantitative reflection about the way in which these two nations have placed themselves in this important index. of measurement, and from the analysis given by this program of the United Nations for development is addressed in a historical way the concept of development, so that based on it is comparatively and statistically identified the phases of comparative evolution of these two nations in the Development context.